Critical Analysis of International Healthcare Systems, Public Health Strategies, and Crisis Management - Alhazoober, Fares Malfoof Amer; Alhazouber, Ibrahim Malfoof Amer; Al-Hazawbar, Abdullah Malfuf Amer; Alhazober, Thabet Salem; Alzamanan, Abdullah Mahdi; Al-Mansour, Ali Muhammad Hadi; Almansour, Hadi Mohammed Hadi; Almansour, Saleh Mohammed Hadi; Alduways, Hamad Hadi Mohmmad; Al-Qarad, Manea Mohamed Hamad (Journal of Ecohumanism, 2024)
Strengths and weaknesses in healthcare systems and public health strategies, along with crisis preparedness and response strategies worldwide, have determined health status globally. This paper also presents a critical discussion of several healthcare models. It analyzes the effectiveness and possible shortcomings of public health approaches with particular emphasis on crisis interventions in pandemics and other types of health catastrophes. It provides facts on medical achievements and failures in countries with various systems, including the communal system and the private system. It analyzes how they come up with strategies to address ailments. In this paper, the issue of governance in relation to health and access to health care and the development of strong healthcare systems, looking at the current problems and future needs, also appears. Also, we provide solutions for enhancing international healthcare systems and managing crises with an emphasis on equal and sustainable access.